2003
DOI: 10.1074/jbc.m210142200
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Bacterial Aminoacylase Cleaves Odorant Precursors Secreted in the Human Axilla

Abstract: Human axillary odor is known to be formed upon the action of Corynebacteria sp. on odorless axilla secretions. The known axilla odor determinant 3-methyl-2-hexenoic acid was identified in hydrolyzed axilla secretions along with a chemically related compound, 3-hydroxy-3-methylhexanoic acid. The natural precursors of both these acids were purified from non-hydrolyzed axilla secretions. From liquid chromatography/ mass spectrometry analysis, it appeared that the acids are covalently linked to a glutamine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
210
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(217 citation statements)
references
References 30 publications
5
210
0
2
Order By: Relevance
“…Recently, researchers at Givaudan (Natsch et al, 2003) identified 3-methyl-3-hydroxylhexanoic acid (HMHA) as an additional important axillary odor constituent; how-ever, the olfactory threshold for this compound has not yet been reported. Qualitatively, this compound has a cuminlike, "sweaty" note reminiscent of E-3M2H, but more pungent (data not shown).…”
Section: Source and Signal: Axillary Chemistry And Pheromone Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers at Givaudan (Natsch et al, 2003) identified 3-methyl-3-hydroxylhexanoic acid (HMHA) as an additional important axillary odor constituent; how-ever, the olfactory threshold for this compound has not yet been reported. Qualitatively, this compound has a cuminlike, "sweaty" note reminiscent of E-3M2H, but more pungent (data not shown).…”
Section: Source and Signal: Axillary Chemistry And Pheromone Creationmentioning
confidence: 99%
“…The structure of ASOB1 remains to be fully elucidated but it too appears to carry acidic molecules. The Givaudan group (Natsch et al, 2003) has suggested that a nonodorous precursor they isolated, an amide of 3-methyl-3-hydroxylhexanoic acid and glutamine (N␣-3-hydroxy-3-methyl-hexenoyl-glutamine; HMHA-Gln), is the actual precursor. However, due to their collection procedure, it is difficult to say that the 3M2H and/or HMHA is not initially intercathelated within ApoD.…”
Section: Source and Signal: Axillary Chemistry And Pheromone Creationmentioning
confidence: 99%
“…The synthesis of reference compounds has been described before (Natsch et al 2003(Natsch et al , 2006.…”
Section: Generalmentioning
confidence: 99%
“…The aqueous phase was lyophilized for 16 hours and re-suspended in 0.7 ml H 2 O. A 0.4 ml sample of this concentrated aqueous extract was treated with a large excess of the recombinant enzyme N-AGA (4.5 mg per sample, produced and purified as described before; Natsch et al 2003) to ensure complete hydrolysis of the Gln conjugates. After 4 hours incubation at 368 C, 30 ml of 1 M HCl and 50 mg NaCl were added and the sample was extracted with 100 ml methyl-tert-butyl-ether (MTBE).…”
Section: Collection Of Axilla Secretions and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation